Methods for Accuracy Increasing of Solid Brittle Materials Fracture Toughness Determining - V. A. Lapitskaya; T. A. Kuznetsova; S. A. Chizhik; B. Warcholinski (Приборы и методы измерений)
Method for determining of the fracture toughness of brittle materials by indentation is described. The critical stress intensity factor KIC quantifies the fracture toughness. Methods were developed and applied to improve the accuracy of KIC determination due to atomic force microscopy and nanoindentation. It is necessary to accurately determine parameters and dimensions of the indentations and cracks formed around them in order to determine the KIC . Instead of classical optical and scanning electron microscopy an alternative high-resolution method of atomic force microscopy was proposed as an imaging method.Three methods of visualization were compared. Two types of crack opening were considered: along the width without vertical displacement of the material and along the height without opening along the width. Due to lack of contact with the surface of the samples under study, the methods of optical and scanning electron microscopy do not detect cracks with a height opening of less than 100 nm (for optical) and less than 40–50 nm (for scanning electron microscopy). Cracks with opening in width are determined within their resolution. Optical and scanning electron microscopy cannot provide accurate visualization of the deformation area and emerging cracks when applying small loads (less than 1.0 N). The use of atomic force microscopy leads to an increase in accuracy of determining of the length of the indent diagonal up to 9.0 % and of determining of the crack length up to 100 % compared to optical microscopy and up to 67 % compared to scanning electron microscopy. The method of atomic force microscopy due to spatial three-dimensional visualization and high accuracy (XY ± 0.2 nm, Z ± 0.03 nm) expands the possibilities of using indentation with low loads.A method was proposed for accuracy increasing of KIC determination by measuring of microhardness from a nanoindenter. It was established that nanoindentation leads to an increase in the accuracy of KIC determination by 16–23 % and eliminates the formation of microcracks in the indentation.